Are we on the same wavelength? Supervisor-subordinate cognitive style congruence and its association with supervisors’ self-awareness through leader member exchange - AlReshaid, Faisal; Erturk, Alper; Alkhayyat, Razan; Abdallah, Farid; Abidi, Oualid; De La Roche, Marcelle (Frontiers in Psychology, 2025)
IntroductionLeaders’ self-awareness is essential to leadership effectiveness. Cognitive styles—how individuals perceive and process information—are key factors in fostering self-awareness. Drawing on Social Identity Theory (SIT), this study explores whether cognitive style congruence between supervisors and subordinates enhances supervisors’ self-awareness, and whether Leader-Member Exchange (LMX) mediates this relationship.MethodsWe used a time-lagged dyadic design and multilevel polynomial regression to analyze data from 189 subordinates and 36 supervisors. Cognitive styles were measured across three dimensions: knowing, planning, and creating. We assessed congruence between supervisors and subordinates and tested LMX as a mediator of its relationship with supervisors’ self-awareness in the context of transformational leadership.ResultsFindings show that LMX fully mediates the relationship between cognitive style congruence (for knowing and creating styles) and supervisors’ self-awareness. Additionally, LMX is highest when supervisors and subordinates share high congruence in these styles. No significant effects were found for the planning style.DiscussionThe study highlights the value of aligning cognitive styles in leader–follower pairs. High cognitive congruence enhances LMX quality, which in turn fosters leader self-awareness—an important precursor to transformational leadership effectiveness.